PENGARUH KOMITMEN ORGANISASI, MOTIVASI DAN INSENTIF TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SURYA AGROLIKA REKSA SINGINGI HILIR - Iswanda, Iswanda; Marnis, Marnis; Rifqi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the influence of organizational commitment, motivation, and incentive partially or simultaneously on the job satisfaction employees at PT. surya agrolika reksa singing hilir. The population in this study were all employees totaling 121 employees and 93 employees were sampled by using the formula slovin, using instrumental testing the validity, reliability and classic assumption test. The analytical method used in this study is descriptive analysis and multiple linear regression analysis using SPSS 21 for windows. From the results of the testing that has been done, simultane ous regression test (F-test) showed that the variables of organizational commitment, motivation and incentive simultaneously significant effecton job satisfaction employees. And the results of the partial test (t test) showed that the variables of organizational commitment, motivation and incentive partially significant effect on job satisfaction employees. The result of the calculation of the coefficient of determination (R2) is equal to 0,273, which means, organizational commitment, motivation, and incentive affect the job satisfaction employees amounted to 27,3%, while the remaining 72.7% is influenced by other variables that no tex amined in this study.Keywords : Organizational Commitmen, Motivation, Incentive, and Job Satisfaction Employees.